2023
DOI: 10.3389/fmed.2023.1209886
|View full text |Cite
|
Sign up to set email alerts
|

Quantum molecular resonance electrotherapy (Rexon-Eye) for recalcitrant dry eye in an Asian population

Valencia Hui Xian Foo,
Yu-Chi Liu,
Bryan Tho
et al.

Abstract: ObjectivesTo assess the safety, efficacy, patients’ satisfaction and acceptability of Rexon-Eye electrotherapy in treating Asian severe dry eye disease (DED) patients.MethodsProspective parallel-arm pilot study recruiting 40 DED Chinese patients with >moderate recalcitrant DED (Contact Lens Research Unit [CCLRU] > grade 2). Subjects were randomized into 2 groups, undergoing four weekly treatment sessions each: group 1 received full treatment power; group 2 received control treatment (power 1 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In this study, the absence of reported AEs after QMR treatment aligns with the findings from other studies conducted by Ferrari et al [ 30 ], Trivli et al [ 32 ], Kavroulaki et al [ 31 ], and Foo et al [ 33 ]. This consistent pattern of safety across multiple studies underscores the robustness of QMR as a safe therapeutic option for DED.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, the absence of reported AEs after QMR treatment aligns with the findings from other studies conducted by Ferrari et al [ 30 ], Trivli et al [ 32 ], Kavroulaki et al [ 31 ], and Foo et al [ 33 ]. This consistent pattern of safety across multiple studies underscores the robustness of QMR as a safe therapeutic option for DED.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have evaluated the effects of QMR treatment on DED symptoms and signs [ 29 33 ]. Pedrotti et al [ 29 ] reported that 12 sessions of QMR treatment significantly improved OSDI questionnaire, TBUT, CFS, and ST after 1 year of follow-up in patients with ADDE.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations